The Relevance of Judicial Beliefs in the Negative Proof System of Article 183 of the Criminal Procedure Code: Analysis of Surabaya District Court Decision Number 454/Pid.B/2024/Pn.Sby: Relevansi Keyakinan Hakim dalam Sistem Pembuktian Negatif Pasal 183 KUHAP: Analisis Putusan Pengadilan Negeri Surabaya Nomor 454/Pid.B/2024/Pn.Sby - Ahmad Bagus Aditia; Muchamad Iksan (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Judicial conviction is a central component of Indonesia’s criminal justice system, which adopts the negative proof theory under Article 183 KUHAP. Specific Background: Growing discrepancies between judicial conviction and legally valid evidence, illustrated by Surabaya District Court Decision Number 454/Pid.B/2024/PN.Sby, have raised concerns regarding doctrinal consistency and judicial practice. Knowledge Gap: Limited studies integrate normative analysis, case-based evaluation, and Islamic legal perspectives to define the boundaries of judicial conviction. Aims: This study examines the relevance and limitations of judicial conviction within the negative proof model and assesses its application in the referenced court decision, complemented by Islamic jurisprudential insights. Results: Findings indicate that although the negative proof system remains normatively sound, judicial practice reveals deviations when conviction becomes overly subjective and insufficiently grounded in evidence; Islamic law emphasizes that judicial belief must be based on proof and moral accountability. Novelty: This research offers an integrative framework combining normative doctrine, case analysis, and Islamic legal principles to reinterpret the objective limits of judicial conviction. Implications: Strengthening objective standards, judicial integrity, and ethical safeguards is necessary to ensure proper application of Article 183 KUHAP and to restore public trust in judicial institutions. Highlights: The negative proof system requires judicial conviction to be firmly grounded in valid evidence. The Surabaya court case illustrates how subjective conviction can distort legal reasoning. Islamic legal principles reinforce the need for moral accountability in judicial decision-making. Keywords: Judicial Conviction, Negative Proof Theory, Article 183 KUHAP, Judicial Integrity, Islamic Legal Perspective